Vector-Matrix Implementation of the Integrated Method of Recovery of Input Signals of Nonlinear Dynamic Systems - Ivaniuk, Vitalii; Verlan, Anatolii; Fedorchuk, Volodymyr; Ponedilok, Vadym (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
In the article the method of signal reconstruction at the input of nonlinear dynamic objects based on the application of vector-matrix approach to solving polynomial Volterra integral equations of the first kind of the second degree using a differential regularization operator is studied.